Psychiatric morbidities of elderly psychiatry out-patients in a tertiary-care hospital - Shakya, DR (Journal of College of Medical Sciences-Nepal, 2012)
With the rise in life expectancy, the elder population is increasing. Morbidity profiles of elderly people may indicate different needs and priorities. This study aims to sort out referral pattern, attitude about psychiatric referral and morbidity profile among elderly psychiatric outpatients in a general hospital. A total of 100 consecutive elderly (>55 years) out-patients in psychiatry OPD coming into contact of the investigator and giving informed consent were enrolled. Diagnoses were made according the ICD-10. More (54%) were female, mainly of age, 55-70 years (79%). Main ethnicity groups seeking care were Mongol (32%), Brahmin (25%), indigenous Terai tribes (14%) and Newar (11%). People from cities and semi-urban settings predominated the study. Referrals made most commonly by the departments were medicine, family medicine, surgery and ENT. More than a fourth (28%) were dissatisfied and questioned about the referral to psychiatric service. Greater proportions (71%) were comfortable and happy about psychiatry referral. Mood related and physical complaints each were presenting complaints in about half of subjects. Major psychiatric diagnoses were mood affective, anxiety, substance use and organic psychiatric disorders. Great majority had physical co-morbidity. Common mental disorders among elderly psychiatry out-patients were mood affective, anxiety and substance use disorders. A significant number of elderly psychiatry out patients had physical comorbidity. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 1-8 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6735